Difference between revisions of "008A Sample Final A, Question 1"
Jump to navigation
Jump to search
Line 3: | Line 3: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Foundations: | + | ! Foundations: |
|- | |- | ||
|1) How would you find the inverse for a simpler function like <math>f(x) = 3x + 5</math>? | |1) How would you find the inverse for a simpler function like <math>f(x) = 3x + 5</math>? | ||
Line 20: | Line 20: | ||
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 1: | + | ! Step 1: |
|- | |- | ||
|We start by replacing f(x) with y. | |We start by replacing f(x) with y. | ||
Line 28: | Line 28: | ||
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;" | {|class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 2: | + | ! Step 2: |
|- | |- | ||
|Now we swap x and y to get <math>x = \log_3(y + 3) - 1</math> | |Now we swap x and y to get <math>x = \log_3(y + 3) - 1</math> | ||
Line 36: | Line 36: | ||
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;" | {|class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 3: | + | ! Step 3: |
|- | |- | ||
|From <math>x = \log_3(y + 3) - 1</math>, we add 1 to both sides to get | |From <math>x = \log_3(y + 3) - 1</math>, we add 1 to both sides to get | ||
Line 46: | Line 46: | ||
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;" | {|class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 4: | + | ! Step 4: |
|- | |- | ||
|After subtracting 3 from both sides we get <math>y = 3^{x+1}-3</math>. Replacing y with <math>f^{-1}(x)</math> we arrive at the final answer that | |After subtracting 3 from both sides we get <math>y = 3^{x+1}-3</math>. Replacing y with <math>f^{-1}(x)</math> we arrive at the final answer that | ||
Line 54: | Line 54: | ||
{|class = "mw-collapsible mw-collapsed" style = "text-align:left;" | {|class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Final Answer: | + | ! Final Answer: |
|- | |- | ||
|<math>f^{-1}(x) = 3^{x+1} - 3</math> | |<math>f^{-1}(x) = 3^{x+1} - 3</math> |
Revision as of 22:49, 25 May 2015
Question: Find for
Foundations: |
---|
1) How would you find the inverse for a simpler function like ? |
2) How do you remove the in the following equation: |
Answers: |
1) you would replace f(x) by y, switch x and y, and finally solve for y. |
2) By the definition of when we write the equation we mean y is the number such that |
Solution:
Step 1: |
---|
We start by replacing f(x) with y. |
This leaves us with |
Step 2: |
---|
Now we swap x and y to get |
In the next step we will solve for y. |
Step 3: |
---|
From , we add 1 to both sides to get |
Now we will use the relation in Foundations 2) to swap the log for an exponential to get |
. |
Step 4: |
---|
After subtracting 3 from both sides we get . Replacing y with we arrive at the final answer that |
Final Answer: |
---|